Brain-based limitations in attention and secondary task engagement during high-fidelity driving simulation among young adults. Issue 8 (22nd May 2020) - Banz, Barbara C.; Wu, Jia; Camenga, Deepa R.; Mayes, Linda C.; Crowley, Michael J.; Vaca, Federico E.
Abstract : Distracted driving remains a leading factor in fatal motor vehicle crashes, particularly in young drivers. Due to ongoing neuromaturation, attention capabilities are changing and improving throughout young adulthood. Here, we sought to bridge neuroscience with driving simulation by evaluating the effects of driving on attention processing through a selective auditory attention task. Participants (18–25 years old) engaged in an auditory attention task during LOAD (driving a high-fidelity simulator) and No-LOAD conditions (sitting in the parked simulator). For the auditory task, participants responded to a target auditory tone in a target ear. The event-related potential components, collected from frontal and posterior regions, P2 and P3, were used to evaluate attention processing across LOAD and No-LOAD conditions for attended and unattended stimuli. Data from 24 participants were evaluated in repeated measures ANOVAs, considering interactions between load and attention conditions for the P2 and P3 components of the cortical region. We observed a significant difference between response to attended and unattended stimuli for posterior P2 and P3 responses at the frontal and posterior midline sites. Comparing LOAD and No-LOAD conditions, there was a significant difference for P2 response at the posterior site and P3 response at the frontal site. A significant interaction between load and attended stimuli was found for P3 response at the posterior site. These data document differences in neural processing of auditory stimuli during high-fidelity simulated driving versus sitting parked in the simulator. Findings suggest the cognitive load of driving affects auditory attention.